2018
DOI: 10.1515/ijsl-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

“In the mouth of an aborigine”: language ideologies and logics of racialization in the Linguistic Survey of India

Abstract: TheLinguistic Survey of India(LSI), edited and compiled by George Abraham Grierson, was the first systematic effort by the British colonial government to document the spoken languages and dialects of India. While Grierson advocated an approach to philology that dismissed the affinity of language to race, theLSImobilizes a complex, intertextual set of racializing discourses that form the ideological ground upon which representations of language were constructed and naturalized. I analyze a sub-set of theLSI’s v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…He also revised Gumperz's insights into South Asian sociolinguistic complexity to argue that the region is a place in which multiple languages are needed to fulfill social functions and that people tend to accommodate each other's multilingual practices, in contrast to the West and its history of standardization through national boundaries and state institutions (see Satyanath 2021). This argument has been influential in more recent work (Canagarajah 2013, Khubchandani 1997. Several important volumes of essays were published, the first as a result of a set of presentations at the 1957 meetings of the American Anthropological Association (Ferguson & Gumperz 1960).…”
Section: Sociolinguistics Of Indiamentioning
confidence: 93%
See 1 more Smart Citation
“…He also revised Gumperz's insights into South Asian sociolinguistic complexity to argue that the region is a place in which multiple languages are needed to fulfill social functions and that people tend to accommodate each other's multilingual practices, in contrast to the West and its history of standardization through national boundaries and state institutions (see Satyanath 2021). This argument has been influential in more recent work (Canagarajah 2013, Khubchandani 1997. Several important volumes of essays were published, the first as a result of a set of presentations at the 1957 meetings of the American Anthropological Association (Ferguson & Gumperz 1960).…”
Section: Sociolinguistics Of Indiamentioning
confidence: 93%
“…Ganti (2016) describes the paradox whereby actors in Bollywood films increasingly use regional rather than standardized varieties of Hindi while English has become the dominant language of interaction in the industry off-screen. Scholars observe that while English is ideologically contrasted with regional and local vernaculars, English words and phrases are also deeply integrated into local linguistic practices (Canagarajah 2013, Ramanathan 2005 (2016) shows how young adults in Tamil Nadu, India, adjust the amount of English in their Tamil speech according to the norms of particular groups. If they do not speak English well enough they may be thought to be "local" or uneducated, but if they speak it "too well" they may be considered snobbish (Nakassis 2016, p. 112).…”
Section: Global Englishmentioning
confidence: 99%
“…Such assessments, Jonathan Rosa argues, are not limited to individualized speakers, but rather “invoke broader ideas about the (in)competence and (il)legitimacy of entire racialized groups” (2016, 163–64). These interpretations are alimented by long‐standing racist, colonial tropes of (in)competent populations that reinforce “essentializing relationships between language, ethnicity and personhood” (Carlan, 2018, 118; see also Bauman and Briggs, 2003; Nakassis and Annamalai, 2020). Not only are these discourses mobilized to delegitimize the speech practices of racialized actors, but they also serve moralizing agendas about falling language standards that are often aligned with (not very successfully) veiled racist tropes.…”
Section: Standards Models and Speakersmentioning
confidence: 99%
“…This includes the introduction of a census but also extends to linguistic scholarship such as the Linguistic Survey of India (LSI) (1903–1928), undertaken by George Abraham Grierson. In her examination of the LSI, Hannah Carlan demonstrates how the objectification of language “as a natural object” led to “essentialized portraits of ‘weak’ and ‘strong’ languages,” characteristics that were then transferred to its speakers' “intellectual capacities” (2018, 101). These raciolinguistic ideologies also informed colonial debates over the medium of education for Indians (see, e.g., Annamalai, 2005; Evans, 2002; Pennycook, 1998) in which advocates of English education drew on discourses of civilization and enlightenment and the construction of the inherently “superior” language of English as a means to access science, modernization, and “the benefits of European knowledge” (Annamalai, 2005; Pennycook, 1998, 75).…”
Section: Colonial and Classed Contours Of English In Indiamentioning
confidence: 99%
“…Such work seeks to understand how speakers use an array of semiotic modalities to co‐constitute and reproduce political economic formations in everyday life (Pigg 2001; Pinto 2004; Heritage and Clayman 2010; Gal, Kowalski, and Moore 2015). While many studies have demonstrated the importance of language for state formation and nation‐building (Ayres 2012; Anderson 1991), recent scholarship has emphasized how the state is produced through material artifacts:how forms of writing, documentation, enumeration, mapping, and more recently digitization are key semiotic technologies through which the state attains its aura of bureaucratic rationality (Hull 2003; 2012a; 2012b; V. Das 2004; Weber 2009; Mathur 2012; Gupta 2012; Mathur 2016; Carlan 2018; In Press; Dandurand 2019). Key to this process is the erasure of social actors, such that bureaucratic decisions, knowledge, and policies may be reproduced through context‐independent logics (Irvine and Gal 2000; Gal and Irvine 2019; Biruk 2018; Appel 2019; Kockelman 2016).…”
Section: Bureaucracy Collectivization Erasurementioning
confidence: 99%